Implementasi Model Pembelajaran Cooperative Integrated Reading And Composition dalam Meningkatkan Keterampilan Mengapresiasi Cerita Fiksi Bagi Siswa Kelas V SD Negeri 228 Tunreng Tullue Kabupaten Bone - Hajja Bunga Tang (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This research is based on the reality on the ground that there are still many students of SD Negeri 228 Tunreng Tullue having difficulty in appreciating fictional stories. To overcome this difficulty, an action was taken using the CIRC type of cooperative learning. This study aims (1) to determine the implementation of CIRC type cooperative learning in appreciating fictional stories in fifth grade students of SD Negeri 228 Tunreng Tullue, (2) to determine the level of achievement of fifth grade students of SD Negeri 228 Tunreng Tullue in appreciating fictional stories through cooperative learning model type. CIRC, and (3) through the CIRC type of cooperative learning model, it can improve the ability of Class V students of SD Negeri 228 Tunreng Tullue in appreciating fiction stories. This research is a classroom action research with the research subjects are all fifth grade students of SD Negeri 228 Tunreng Tullue, Bone Regency, South Sulawesi Province, as many as 14 students consisting of 6 girls and 8 boys in 2021.